Third human challenge trial conference, Oxford, United Kingdom, February 6–7, 2020, a meeting report. (July 2020) - ,; Balasingam, Shobana; Bejon, Philippe; Berthels, Nele; Bull, Susan; Catchpole, Andrew; Chi, Primus; Chilengi, Roma; Cox, Rebecca; Davies, Hugh; Durbin, Anna; Emary, Kate; et al.
Abstract: The third Human Challenge Trial Meeting brought together a broad range of international stakeholders, including academia, regulators, funders and industry, with a considerable delegation from Low- and Middle-Income Countries. Controlled human infection models (CHIMs) can be helpful to study pathogenesis and for the development of vaccines. As challenge agents are used to infect healthy volunteers, ethical considerations include that the challenge studies need to be safe and results should be meaningful. The meeting provided a state-of-the-art overview on a wide range of CHIMs, including viral, bacterial and parasitic challenge agents. Recommendations included globally aligned guidance documents for CHIM studies; further definition of a CHIM, based on the challenge agent used; standardization of methodology and study endpoints; capacity building in Low- and Middle-Income Countries, in performance as well as regulation of CHIM studies; guidance on compensation for participation in CHIM studies; and preparation of CHIM studies, with strong engagement with stakeholders. Highlights: Human challenge trials can help to study pathogenesis and develop vaccines. There is a need for globally aligned guidance documents for human challenge trials. Standardization allows to compare study outcomes and perform meta-analyses. Capacity building in performance and regulation is needed in LMIC. Compensation of participants needs to be considered carefully.